The arts - Bliss, Henry Evelyn, 1870-1955 (Bliss bibliographic classification ;, 2007)
Outline of the complete BC2 classification -- Second outline of the complete BC2 classification -- Volumes in the series -- The Bliss Classification Association -- Officers of the Association and members of the Committee -- Bliss Classification Association : Subscription form for New Members -- Introduction to Class W The Arts -- 1 Nature and purpose of Class W -- 2 Library classification -- 3 BC2 classification -- 4 Scope of the Arts class and its place in a general classification -- 5 Structure of Class W The Arts -- 6 Facet structure of Class W The Arts